2017
DOI: 10.1159/000455870
|View full text |Cite
|
Sign up to set email alerts
|

Small Choroidal Melanoma Revealed by a Large Extrascleral Extension

Abstract: Aims: Orbital extraocular extension of choroidal melanoma is very rare with small melanomas. We report the case of a patient whose small choroidal melanoma was initially overlooked and was revealed by a large extrascleral extension. Methods: A 48-year-old Caucasian woman presented with sudden total visual loss in the right eye. Multicolor imaging of the fundus showed right optic disc edema and an orange and green lesion near the optic disc. The diagnosis of unilateral optic neuritis was made. Magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
2
10
0
1
Order By: Relevance
“…It should be diagnosed in order to be taken into account in the treatment plan. We found extrascleral extension in 7% of the UM, consistent with current literature [ 27 , 29 – 31 ]. Interestingly, in the present study, all observed extrascleral extensions occurred in small tumors with a maximum prominence of 4.8 mm, although in general, it occurs more commonly in medium or large tumors [ 29 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It should be diagnosed in order to be taken into account in the treatment plan. We found extrascleral extension in 7% of the UM, consistent with current literature [ 27 , 29 – 31 ]. Interestingly, in the present study, all observed extrascleral extensions occurred in small tumors with a maximum prominence of 4.8 mm, although in general, it occurs more commonly in medium or large tumors [ 29 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found extrascleral extension in 7% of the UM, consistent with current literature [ 27 , 29 – 31 ]. Interestingly, in the present study, all observed extrascleral extensions occurred in small tumors with a maximum prominence of 4.8 mm, although in general, it occurs more commonly in medium or large tumors [ 29 , 32 ]. Extrascleral extension often develops along scleral canals, via perivascular or perineural invasion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When a choroidal melanoma involves the optic nerve, the fundus may have a similar manifestation of optic neuritis; MRI may show the tumor as a mass adjacent to the optic nerve. However, ultrasound evaluation can show the absence of an echo and reveal intraocular components, thus aiding in diagnosis of the mass ( 40 ). Nevertheless, for small choroidal melanomas, the specificity of ultrasound involving subretinal fluid is low, because such tumors cannot be distinguished from retinal thickening, cystic changes, and pigment epithelial detachment ( 41 ).…”
Section: Diagnosis Of Choroid Melanomamentioning
confidence: 99%